Evaluation of organic products and bioagents against Sclerotinia sclerotiorum causing white rot of peas (Journal of Plant Disease Sciences, 2023)
White rot of pea is caused by dreaded, nectrotrophic and polyphagous fungus Sclerotinia sclerotiorum. White rot has become a limiting factor in pea cultivation due to monoculture and extensive pea cultivation in Himachal Pradesh, India. In vitro evaluation of different organic enriched composts revealed that aqueous and crude extract of Himslurry had shown maximum mycelial inhibition of 84.66 and 89.63 respectively at 25% concentration. In case of organic products, both aqueous and crude extracts of Cow urine and Jiwamrit had shown cent per cent mycelial inhibition at 5% concentration.  Among botanicals, aqueous and crude extracts of Vitex negundo had shown maximum mycelial inhibition of 48.15 and 90.37% respectively. A strain SMA-5 of Trichoderma harzianum showed maximum mycelial inhibition of 70.74% against Sclerotinia sclerotiorum.
Keywords: Pea; Sclerotinia; sclerotiorum; Efficacy; Botanicals; Bioagents